Plan de exportanción de blusas otavaleñas bosdadas a mano para la empresa Sinaí Artesanías de Otavalo-Ecuador hacia el mercado español - Fueres, Gladys R. (2017)
The present research project consists in a design proposal for a plan of export of otavaleñas embroidered blouses of the Sinaí Artesanías Company, clothing cultural addressed to indigenous women resident in the city of Barcelona-Spain.